The influence of product quality, price perception and brand image on consumer satisfaction of Yamaha NMAX Motorcycles in Denpasar Bali - Putu Ayu Lalita Srivisakha; Trianasari, Trianasari; Ni Made Suci (Jurnal Ekonomi, 2024)
The aim of this research is to ascertain how two or more factors interact. The research location is the Yamaha Agung Motor Dealer. The subjects in this research were all customers who used Yamaha NMAX motorbikes in the Denpasar Bali area. The impact of brand image, pricing perception, and product quality on customer satisfaction is the focus of this study. Purposive sampling was used to select 190 participants to become the research sample. Google Forms was used to complete the questionnaire as part of the data collection strategy. This research uses multiple linear analysis methods to determine how big the influence of several independent and dependent variables is. The research results show: (1) The Yamaha NMAX motorcycle customers in Denpasar's consumer satisfaction is largely influenced by product quality, as indicated by the product quality variable's significance value of 0.000, which is less than the predetermined significance threshold of 0.05. (2) the variable pricing on consumer satisfaction finds that pricing has a somewhat significant impact on customer satisfaction, with a significance value of 0.001, which is less than the designated significance threshold of 0.05 using Yamaha NMAX motorbikes in Denpasar. (3) variable Brand image on consumer satisfaction obtained a significance value of 0.040, below the predetermined 0.05 level of significance, indicating that brand image has a somewhat meaningful impact on consumer satisfaction of Yamaha NMAX motorbike users in Denpasar.